The Effect of Mobile Learning on the Study Results of Arab Language Students of MTs-TI Pariangan - Ikhlas, Rifki Zaitul; Abidin, Munirul (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. In today’s digital era, the use of technology in education is becoming increasingly important. Mobile learning in the form of Articulate Storyline application offers easy access and interactivity that can enrich students’ learning experience. However, not many studies have specifically investigated the impact of using the application on student learning outcomes at MTs-TI Pariangan. Purpose. This study aims to evaluate the effect of using the Articulate Storyline application on students’ Arabic learning outcomes at MTs-TI Pariangan. Factors that influence the effectiveness of the app in improving academic achievement will be scrutinised to provide greater insight into the effectiveness of the app. Method. The research method used is an experimental study with a pre-test and post-test design. The research sample was 8th grade students of MTs-TI Pariangan consisting of 20 students. Data was collected through an initial test before the use of the application and a final test after the period of application use. Results. The results of this study showed a significant improvement in student learning outcomes after using the Articulate Storyline app. Students who actively used the application showed greater improvement in material understanding and academic achievement compared to those who did not use the application. The findings support the hypothesis that the use of the Articulate Storyline application has a positive effect on student learning outcomes at MTs-TI Pariangan. Conclusion. This study shows that the use of Articulate Storyline mobile learning application significantly improves the Arabic learning outcomes of grade 8 students of MTs-TI Pariangan. Validity and reliability tests confirm that the instruments used have high consistency and reliability. The results of statistical analysis showed a significant difference between the pre-test and post-test scores, with an increase in the average score from 65.00 to 80.50.